PENGARUH OPERATING LEVERAGE DAN FINANCIAL LEVERAGE TERHADAP RETURN ON EQUITY PADA PERUSAHAAN PROPERTY DAN REAL ESTAT - Soleh Rosyad; Winni Indriani (Universitas La Tansa Mashiro, 2018)
This study aims to determine the effect of operating leverage and financial leverage on return on equity on property and real estate companies listed on the Indonesia Stock Exchange. The research method used is a quantitative method with a population of all Property and Real Estate companies, a sample of 6 companies. Data analysis techniques in this study multiple linear regression analysis, determination coefficient, t test and F test in SPSS 20 For Windows. The results of the study based on the F test show that Operating Leverage and Financial Leverage simultaneously have a significant effect on Return On Equity, this is evidenced by a significance level smaller than 0.05, namely 0.043. Based on the results of the t test it is known that Financial Leverage does not partially affect Return On Equity, this is evidenced by a significance level greater than 0.05, namely 0.553. Based on the results of the t test also known that the Operating Leverage partially has a significant positive effect on Return On Equity, this is evidenced by a significance level smaller than 0.05, namely 0.018. The results of the analysis show that the adjusted coefficient of determination (Adjusted R square) is 0.149 or 14.9%.